2021
DOI: 10.1186/s12870-021-03331-9
|View full text |Cite
|
Sign up to set email alerts
|

A rapid, simple, and highly efficient method for VIGS and in vitro-inoculation of plant virus by INABS applied to crops that develop axillary buds and can survive from cuttings

Abstract: Background Virus-induced gene silencing (VIGS) is one of the most convenient and powerful methods of reverse genetics. In vitro-inoculation of plant virus is an important method for studying the interactions between viruses and plants. Agrobacterium-based infiltration has been widely adopted as a tool for VIGS and in vitro-inoculation of plant virus. Most agrobacterium-based infiltration methods applied to VIGS and virus inoculation have the characteristics of low transformation efficiencies, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…Notably, the most commonly used agroinfiltration method for VIGS is the syringe infiltration of leaves. This methods has been applied in VIGS studies on a broad range of plant species: Brassica oleracea [ 3 ], Gerbera hybrid [ 45 ], Solanum lycopersicum [ 46 ], lettuce [ 47 ], Oryza sativa [ 48 ], Triticum aestivum [ 31 ], Eschscholzia californica [ 49 ], Capsicum annuum [ 50 ], Gossypium hirsutum [ 51 ]. In sunflower [ 38 ], using syringe infiltration, the authors observed the photo-bleaching phenotype in expanded leaves and leaflets near the inflorescence.…”
Section: Discussionunclassified
“…Notably, the most commonly used agroinfiltration method for VIGS is the syringe infiltration of leaves. This methods has been applied in VIGS studies on a broad range of plant species: Brassica oleracea [ 3 ], Gerbera hybrid [ 45 ], Solanum lycopersicum [ 46 ], lettuce [ 47 ], Oryza sativa [ 48 ], Triticum aestivum [ 31 ], Eschscholzia californica [ 49 ], Capsicum annuum [ 50 ], Gossypium hirsutum [ 51 ]. In sunflower [ 38 ], using syringe infiltration, the authors observed the photo-bleaching phenotype in expanded leaves and leaflets near the inflorescence.…”
Section: Discussionunclassified
“…This reverse genetic technique adopts viral vectors carrying a target gene fragment to produce dsRNA and then triggers RNA-mediated gene silencing [16]. One of the most widely used viral delivery vectors is tobacco rattle virus (TRV) due to its simple expression in meristematic tissue [17]. VIGS has many advantages compared with other loss-of-function approaches Undoubtedly, P. lactiflora Pall.…”
Section: Introductionmentioning
confidence: 99%
“…This reverse genetic technique adopts viral vectors carrying a target gene fragment to produce dsRNA and then triggers RNA-mediated gene silencing [16]. One of the most widely used viral delivery vectors is tobacco rattle virus (TRV) due to its simple expression in meristematic tissue [17]. VIGS has many advantages compared with other loss-of-function approaches because it allows phenotypes to achieve rapid performance, provides time-saving experimental processes, does not require complex tissue culture, and has the potential to silence either individual or multiple members of a gene family [18].…”
Section: Introductionmentioning
confidence: 99%